Optimization of Mobile Attendance System with Haversine Formula Method for Field Work Practice Students - Alkodri, Ari Amir; Fitriyani, F; Isnanto, Burham; Sari, Melati Suci Maya; Andrika, Yuyi (IJISTECH (International Journal of Information System and Technology), 2025)
Conventional attendance of Field Work Practice (PKL) students still has various obstacles, such as manipulation of attendance, late recording, and difficulties in validating accurate attendance. In today's digital era, the use of location-based technology is a solution to overcome these problems. Therefore, this study aims to develop and optimize a location-based mobile attendance system by implementing the Haversine Formula Method. This method is used to calculate the distance between the student's GPS coordinates and the predetermined PKL location, so that the system only allows attendance if the student is within a certain radius.With implementation on the Android platform. The main features of this system include real-time location recording, automatic validation based on GPS coordinates, and encrypted data security. Accuracy measurement uses a comparison of the Haversine distance calculation results with a mapping application. The results of the study show that the Haversine Formula method is able to calculate distances with high accuracy, and the system developed can prevent cheating in attendance. Thus, the application of this method can improve transparency, efficiency, and accuracy of recording the attendance of PKL students in real-time, provide convenience for institutions in monitoring the presence of coordinates laboratory location accurately with a distance of ≤ 50 meters, so that the system can determine whether students are within the radius permitted to take attendance at Latitude: -2.123900 and Longitude: 106.788800. at the location of the PKL institution, namely in the ISB Atma Luhur computer laboratory.